Optimization of The Implementation of Regional Financial Supervision In The Regional Government Of Banten Province - Natta Sanjaya; Kismartin Kismartin (Program Pascasarjana Universitas Negeri Makassar, 2021)
Regional financial management supervision activities are carried out as a form to test the accountability and compliance of local governments in the performance of conducting regional financial management. The implementation of financial management supervision is carried out in a multilevel manner and organized by internal and external government agencies. The implementation of internal supervision is carried out through the Sistem Pengendalian Intern Pemerintah (SPIP), further implemented and strengthened by the implementation of internal government supervision by the Aparat Pengawas Internal Pemerintah (APIP), as well as external government supervision carried out by the Audit Board as an independent body. Optimizing the supervisory function of regional financial management in Banten Province needs to be done because there are still many financial management problems faced by the Banten Provincial Government. Of course, the purpose of this study was to find out how efforts to optimize the implementation of regional financial supervision in the Regional Government of Banten Province. Researchers use qualitative research methods with an expiatory approach. This research uses the study of the reliability theory of public sector audits by prioritizing the competence and professionalism of auditors, strong and independent public sector audit institutions, and the existence of clear audit standards. The result obtained is the need to improve the competence and professionalism of auditors even amid a pandemic because the increase in auditor competence is needed to produce optimal supervision, in addition to the need for strengthening independent and credible supervisory institutions.Keywords: Optimization, Supervision, Regional Finance